2021
DOI: 10.1186/s12964-020-00679-7
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Warburg effect by targeting HRD1-PFKP pathway may inhibit breast cancer progression

Abstract: Background Our previous studies have shown that the E3 ubiquitin ligase of HMG-CoA reductase degradation 1 (HRD1) functions as a tumor suppressor, as overexpression of HRD1 suppressed breast cancer proliferation and invasion. However, its role in breast cancer cell glucose metabolism was unclear. Here, our aim was to uncover the role and molecular mechanisms of HRD1 in regulating aerobic glycolysis in breast cancer. Methods The effect of HRD1 on r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is well established that E3 ligases, including SYVN1 can have opposite effects as either tumor suppressors (TS) or oncogenes depending on the context or type of cancer ( 73 75 ). With regards to SYVN1, previous studies have shown that it functions as a tumor suppressor in breast ( 37 , 39 , 41 , 76 , 77 ) and ovarian ( 40 ) cancers. On the contrary, the tumor-promoting (oncogenic) effects of SYVN1 have been revealed in colon cancer ( 78 ), lung cancer ( 79 , 80 ), and hepatocellular carcinoma ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that E3 ligases, including SYVN1 can have opposite effects as either tumor suppressors (TS) or oncogenes depending on the context or type of cancer ( 73 75 ). With regards to SYVN1, previous studies have shown that it functions as a tumor suppressor in breast ( 37 , 39 , 41 , 76 , 77 ) and ovarian ( 40 ) cancers. On the contrary, the tumor-promoting (oncogenic) effects of SYVN1 have been revealed in colon cancer ( 78 ), lung cancer ( 79 , 80 ), and hepatocellular carcinoma ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…45 In addition, the E3 ubiquitin ligase of HRD1 (HMG-CoA reductase degradation 1) was also reported to mediate PFKP ubiquitination and degradation. 46 However, such a mechanism has never been described in PFKM. Our study first demonstrated that the stability of both PFKP and PFKM can be regulated by the TRIM21-mediated ubiquitylation; second, we found that PFKP/M interact with MFN2 via MFN2 C-terminus and the interaction facilitates PFKP/M binding to TRIM21; third, by employing the mechanical stretching experiment, we discovered that the PFKP/M-MFN2 interaction as well as PFKP/M ubiquitylation and stability are mechanically regulated; fourth, study by restoring PFKP expression in MFN2 over-expressing VSMCs, and PFK inhibition in the MFN2 knockdown cells demonstrated the functional interaction between MFN2 and PFK activities.…”
Section: Discussionmentioning
confidence: 99%
“…It may reflect that activation of lipid metabolismrelated pathways plays a dominant role in tumorigenesis and progression in BC patients with low-risk scores. Finally, there is a bold idea that BC patients in the high-risk group may benefit from therapy targeting glucose MRGs, such as HK3 (37) and PFKP (38). Meanwhile, the novel therapy targeting genes associated with lipid metabolisms, such as HMGCR (39) and FASN (40), may be effective in those at low risk.…”
Section: Metabolic Characteristics Of the Highand Low-risk Groupsmentioning
confidence: 99%